PENGARUH KECERDASAN EMOSIONAL, KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN PADA CV. PIA FORTA KOTA PROBOLINGGO - Rangga Putra Sujana; Ngatimun Ngatimun; Yekti Rahajeng (Universitas Panca Marga, 2024)
The aim of this research is to determine the influence of the variables of Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior on partial employee performance at CV. Pia Forta Probolinggo City. This type of research uses quantitative research methods with an associative approach, with a sample size of 32 respondents who are CV employees. Pia Forta Probolinggo City using saturated sampling techniques. Validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination (R2) and also the T test are data analysis methods. In this way, from the results of the T Test it is known that there is a positive and significant influence of the variables emotional intelligence, organizational commitment, and organizational citizenship behavior on the performance of CV employees. Pia Forta Probolinggo City.